Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Get immediate and reliable solutions to your questions from a knowledgeable community of professionals on our platform. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To find the [tex]\( z \)[/tex]-coordinate of the point [tex]\((x, y, z)\)[/tex] that satisfies the system of linear equations:
[tex]\[ \begin{array}{l} 5x - y - z = 10 \\ 2x + y + z = 11 \\ y + 5 = z \end{array} \][/tex]
we need to solve the system step-by-step.
1. Start with the third equation:
[tex]\[ y + 5 = z \][/tex]
We can rearrange this to express [tex]\( z \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ z = y + 5 \][/tex]
2. Substitute [tex]\( z = y + 5 \)[/tex] into the first and second equations.
For the first equation:
[tex]\[ 5x - y - (y + 5) = 10 \][/tex]
Simplify this:
[tex]\[ 5x - y - y - 5 = 10 \][/tex]
[tex]\[ 5x - 2y - 5 = 10 \][/tex]
Add 5 to both sides:
[tex]\[ 5x - 2y = 15 \][/tex]
Divide everything by 5:
[tex]\[ x - \frac{2}{5}y = 3 \][/tex]
Multiply everything by 5 to clear the fraction:
[tex]\[ 5x - 2y = 15 \quad \text{(Equation A)} \][/tex]
For the second equation:
[tex]\[ 2x + y + (y + 5) = 11 \][/tex]
Simplify this:
[tex]\[ 2x + y + y + 5 = 11 \][/tex]
[tex]\[ 2x + 2y + 5 = 11 \][/tex]
Subtract 5 from both sides:
[tex]\[ 2x + 2y = 6 \][/tex]
Divide everything by 2:
[tex]\[ x + y = 3 \quad \text{(Equation B)} \][/tex]
3. Now we have a simplified system of two equations:
[tex]\[ \begin{array}{l} 5x - 2y = 15 \quad \text{(Equation A)} \\ x + y = 3 \quad \text{(Equation B)} \end{array} \][/tex]
4. Solve Equation B for [tex]\( x \)[/tex]:
[tex]\[ x = 3 - y \][/tex]
5. Substitute [tex]\( x = 3 - y \)[/tex] into Equation A:
[tex]\[ 5(3 - y) - 2y = 15 \][/tex]
Distribute 5:
[tex]\[ 15 - 5y - 2y = 15 \][/tex]
Combine like terms:
[tex]\[ 15 - 7y = 15 \][/tex]
Subtract 15 from both sides:
[tex]\[ -7y = 0 \][/tex]
Divide by -7:
[tex]\[ y = 0 \][/tex]
6. Substitute [tex]\( y = 0 \)[/tex] back into Equation B:
[tex]\[ x + 0 = 3 \][/tex]
[tex]\[ x = 3 \][/tex]
7. Finally, use [tex]\( z = y + 5 \)[/tex] to find [tex]\( z \)[/tex]:
[tex]\[ z = 0 + 5 \][/tex]
[tex]\[ z = 5 \][/tex]
Hence, the [tex]\( z \)[/tex]-coordinate of the solution is [tex]\( \boxed{5} \)[/tex].
[tex]\[ \begin{array}{l} 5x - y - z = 10 \\ 2x + y + z = 11 \\ y + 5 = z \end{array} \][/tex]
we need to solve the system step-by-step.
1. Start with the third equation:
[tex]\[ y + 5 = z \][/tex]
We can rearrange this to express [tex]\( z \)[/tex] in terms of [tex]\( y \)[/tex]:
[tex]\[ z = y + 5 \][/tex]
2. Substitute [tex]\( z = y + 5 \)[/tex] into the first and second equations.
For the first equation:
[tex]\[ 5x - y - (y + 5) = 10 \][/tex]
Simplify this:
[tex]\[ 5x - y - y - 5 = 10 \][/tex]
[tex]\[ 5x - 2y - 5 = 10 \][/tex]
Add 5 to both sides:
[tex]\[ 5x - 2y = 15 \][/tex]
Divide everything by 5:
[tex]\[ x - \frac{2}{5}y = 3 \][/tex]
Multiply everything by 5 to clear the fraction:
[tex]\[ 5x - 2y = 15 \quad \text{(Equation A)} \][/tex]
For the second equation:
[tex]\[ 2x + y + (y + 5) = 11 \][/tex]
Simplify this:
[tex]\[ 2x + y + y + 5 = 11 \][/tex]
[tex]\[ 2x + 2y + 5 = 11 \][/tex]
Subtract 5 from both sides:
[tex]\[ 2x + 2y = 6 \][/tex]
Divide everything by 2:
[tex]\[ x + y = 3 \quad \text{(Equation B)} \][/tex]
3. Now we have a simplified system of two equations:
[tex]\[ \begin{array}{l} 5x - 2y = 15 \quad \text{(Equation A)} \\ x + y = 3 \quad \text{(Equation B)} \end{array} \][/tex]
4. Solve Equation B for [tex]\( x \)[/tex]:
[tex]\[ x = 3 - y \][/tex]
5. Substitute [tex]\( x = 3 - y \)[/tex] into Equation A:
[tex]\[ 5(3 - y) - 2y = 15 \][/tex]
Distribute 5:
[tex]\[ 15 - 5y - 2y = 15 \][/tex]
Combine like terms:
[tex]\[ 15 - 7y = 15 \][/tex]
Subtract 15 from both sides:
[tex]\[ -7y = 0 \][/tex]
Divide by -7:
[tex]\[ y = 0 \][/tex]
6. Substitute [tex]\( y = 0 \)[/tex] back into Equation B:
[tex]\[ x + 0 = 3 \][/tex]
[tex]\[ x = 3 \][/tex]
7. Finally, use [tex]\( z = y + 5 \)[/tex] to find [tex]\( z \)[/tex]:
[tex]\[ z = 0 + 5 \][/tex]
[tex]\[ z = 5 \][/tex]
Hence, the [tex]\( z \)[/tex]-coordinate of the solution is [tex]\( \boxed{5} \)[/tex].
Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Westonci.ca is committed to providing accurate answers. Come back soon for more trustworthy information.